Vegetation Health of Pioneer Species in the Natural Succession of a Burned Peatland Ecosystem in Liang Anggang - SUSILAWATI SUSILAWATI; Yasinta Nur Shiba; Normela Rachmawati; Mufidah Mufidah; Eny Dwi Pujawati; Eva Prihatiningtyas; Hadi Rosadi (Lambung Mangkurat University-Indonesia, 2026)
Peatland forests in Liang Anggang, Banjarbaru City, play a vital ecological role as carbon sinks, hydrological regulators, and biodiversity buffers. However, these ecosystems are highly vulnerable to recurrent fires, which occur almost annually. Repeated fire events have led to vegetation degradation, declining ecosystem health, and reduced peat capacity to retain water, maintain soil moisture, and support the regeneration of native vegetation. These conditions elevate the risk of ecological disasters and carbon emissions, highlighting the need for vegetation health assessments as a foundation for sustainable restoration strategies.This study evaluated post-fire vegetation health using the Forest Health Monitoring (FHM) approach. The results indicate that the most severe damage occurred in leaves (72%), followed by damage to shoots and buds (11%), and to both upper and lower stems (4–5%). The most common types of damage were leaf and shoot damage (34%) and leaf discoloration (26%), reflecting physiological stress due to increased temperatures and reduced soil moisture after fire events. Damage severity was predominantly classified as light to moderate (10–29%), accounting for 81% of all observed cases.The pioneer vegetation identified includes galam (Melaleuca cajuputi) and acacia (Acacia sp.), which play a significant role in the early stages of ecological succession, although the regeneration of native peatland species remains limited. Overall, vegetation health was categorized as healthy (94%), indicating a strong potential for ecosystem recovery, particularly if hydrological conditions can be effectively maintained. These findings provide a scientific basis for developing sustainable conservation and restoration strategies for the Liang Anggang peatland forest.